Land reform in South Africa: effects on land prices and productivity - Van Rooyen, Jonathan (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2009)
South Africa's land redistribution policy (1994-2008) has been widely publicised, and has come under scrutiny of late from the public, private and government spheres, highlighting a need for research in this area. The research examines progress in South Africa's land redistribution programme in two of KwaZulu-Natal's district municipalities, Uthungulu and iLembe. Specifically the research investigates whether the government has paid above market prices when purchasing sugarcane farmland for redistribution in these districts. Moreover, it is illustrated how productivity on redistributed farms has been affected with the changes in ownership. To investigate the research questions, reviews of theories pertaining to property rights, land reform and market structures were conducted. Moreover, two cases studies were conducted in the districts of Uthungulu and iLembe, with assistance from the Department of Land Affairs, Inkezo Land Company and the South African Cane Growers Association. The case study data indicate that above ordinary market prices have been paid (2004-2006) by the government for sugarcane farmland in the districts concerned, and further that productivity has been negatively impacted 'during' and 'post' transfer, in the majority of cases.
Keywords: Right of property -- South Africa; Land reform -- South Africa; Agriculture and state -- South Africa; Agricultural prices -- South Africa; Land tenure -- Government policy -- South Africa; Land reform -- Economic aspects -- South Africa; Real property -- Prices -- South Africa